Comparison of The Property Players’ Preferences on Housing Prices in Surabaya - Muktiwibowo, Sebastian Arif; Anastasia, Njo (Universitas Diponegoro, Indonesia, 2023)
A landed house is a real estate product that is used to fulfill consumption or investment motives. This study was conducted to compare the preferences of developers, consumers, and investors for housing prices in Surabaya on both motives. Respondents were selected by purposive sampling and obtained 417 respondents. Data collection through questionnaires was conducted offline to developers and online to consumers and investors. Test data used Kendall concordance and Kruskal Wall test to analyze the comparison of developer, consumer, and investor preferences. The results showed that the three players had different preference variables on house prices in Surabaya related to physical quality, brand, location concept, location environment, financial condition, and livability. Developers focus on products (physical quality and housing concept) and brands. Consumers prioritize physical quality, location environment, and financial condition. Furthermore, investors prioritize the physical and environmental quality of the location. Physical quality is a key preference among developers, consumers, and investors. These findings indicate that each party has their own prioritized interests, so their preferences differ according to their motives.